In-betweenness: a postcolonial exploration of sociocultural intergenerational learning through cattle as a medium of cultural expression in Mpembeni, KwaZulu-Natal - Masuku, Lynette Sibongile (Rhodes University, Faculty of Education, Department of Education, 2019)
This case study was conducted in a small rural community called Mpembeni, in South Africa's KwaZulu-Natal province. It was motivated by my observation of high levels of competence in 'cattle knowledge' amongst children coupled with a simultaneous failure at school. I view schools as integral parts of the community and consider them as being influenced by the community, which they in turn influence. This study set out to understand that which embodied informal learning in home/pasture-based contexts as well as formalised learning processes in schools. I used Sociocultural theory as the most congruent of educational theories to surface and illuminate the intergenerational learning processes that were taking place in the area. This warranted my use of research investigation methods that could, in non-intrusive ways, expose the everyday community practices that related to cattle as a particular medium of cultural expression. Ethnography, sourced from anthropology, aided by ethnomethods, was not only compatible with my study and the way in which I wanted to write out the research report, but also with my educational theory and its counterhegemonic intents. To understand the colonialities that framed the discord that embodied home and school as learning contexts, I used postcolonial theory, not only as a lens but as a counterhegemonic response. This theory also informed my research methodology as well as afforded me the reflexivity tools for an examination of my own intergenerational learning and the relational identities of myself as 'Other' in the lives of the research participants. It further facilitated the exploration of the potential for potential hybrid third spaces within the bubbling meeting nodes of the socio-cultural context of school and home/pasture based settings of learning. I observed cattle herding related practices, interviewed children, their parents and/or carers, dipping tank managers, livestock inspectors, community elders and members. I also analysed some of the written and unwritten content that made up the formal and informal based learning processes and reviewed some of the most recent South African Curriculum Statements and related texts on the representations of cattle. I sought views from teachers on their interactions with the people of Mpembeni, whose children they taught. I also explored axes of tension, silences and presences on anything related to cattle in schools. I argue and make a case for the development of thought by African scholars to advance Africa's education rather than aid mimicry and the importation of theories of little congruence and relevance to the African context and Africa's future. The study has made some contributions to new knowledge. This is in its exploration of sociocultural intergenerational methods and techniques that are employed for learning in community contexts, highlighting the importance of surfacing and understanding of children's knowledge and experiences. The study has gone further to deliberate the in-betweenness of school and home learning environments, highlighting and unsilencing silenced, peripherised, new, old, considered irrelevant in the past, context and time congruent and liberatory knowledges. I propose that the knowledges located in these cleavages of difference be utilised to transform and create learning bridges between home and school environments. I propose that those ways of knowing that see others as nothings, be exposed and unlearned. Methods of learning that naturally unfold at home could be replicated at school with a recognition of the intergenerational methods, techniques, practices and the learning values in a critically constructive manner that narrows difference and othering.
Keywords: Postcolonialism; Environmental education -- South Africa; Community education -- South Africa -- KwaZulu Natal; Non-formal education -- South Africa -- KwaZulu Natal; Agricultural education -- South Africa -- KwaZulu Natal; Livestock -- Handling -- South Africa -- KwaZulu Natal; Cattle -- Handling -- South Africa -- KwaZulu Natal; Cattle herding -- South Africa -- KwaZulu Natal; Life skills -- Study and teaching -- South Africa